2021
DOI: 10.1111/acel.13393
|View full text |Cite
|
Sign up to set email alerts
|

Metabolipidomic profiling reveals an age‐related deficiency of skeletal muscle pro‐resolving mediators that contributes to maladaptive tissue remodeling

Abstract: Specialized pro‐resolving mediators actively limit inflammation and support tissue regeneration, but their role in age‐related muscle dysfunction has not been explored. We profiled the mediator lipidome of aging muscle via liquid chromatography‐tandem mass spectrometry and tested whether treatment with the pro‐resolving mediator resolvin D1 (RvD1) could rejuvenate the regenerative ability of aged muscle. Aged mice displayed chronic muscle inflammation and this was associated with a basal deficiency of pro‐reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 45 publications
(106 reference statements)
2
21
0
Order By: Relevance
“…Consistent with previous observations in an analogous model in the rectus femoris (10,25), defects below the critical threshold regenerate, while larger defects result in long-term increases in fibrosis and reductions in contractile force. Using this model of regenerative and degenerative VML, we performed metabolipidomics analysis (40) over a time course to understand signaling factors that contribute to the observed changes in fibrosis. We detected a stark imbalance of pro-inflammatory eicosanoids to pro-resolving lipid mediators in degenerative VML injuries, which correlates with our previous observations of sustained inflammation and persistent neutrophil (10) and macrophage (6) presence following degenerative VML.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous observations in an analogous model in the rectus femoris (10,25), defects below the critical threshold regenerate, while larger defects result in long-term increases in fibrosis and reductions in contractile force. Using this model of regenerative and degenerative VML, we performed metabolipidomics analysis (40) over a time course to understand signaling factors that contribute to the observed changes in fibrosis. We detected a stark imbalance of pro-inflammatory eicosanoids to pro-resolving lipid mediators in degenerative VML injuries, which correlates with our previous observations of sustained inflammation and persistent neutrophil (10) and macrophage (6) presence following degenerative VML.…”
Section: Discussionmentioning
confidence: 99%
“…However, Resolvin D1 (RvD1), which is another member of the D-series resolvin family, was shown to limit neutrophil infiltration into the peritoneum (2) and reduced neutrophils in the lungs after remote organ ischemia reperfusion injury (4) in old animals. Another study demonstrated that RvD1 treatment to aged mice reduced skeletal muscle inflammation and fibrosis, again suggesting a role for D-Series resolvins in limiting inflammation and tissue injury in aging (28). The mechanisms of actions of RvD1 in aging are not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Félix-Soriano et al found that MaR1 was significantly reduced in adipose tissue in aged HFD-induced obese mice compared to young normal controls [ 33 ]. Markworth et al also showed that aged mouse muscle displayed significantly lower MaR1 levels than the young mouse muscle [ 34 ]. These data suggested that ageing is associated with MaR1 deficiency.…”
Section: Discussionmentioning
confidence: 99%